Biomass conversion of saw dust to a functionalized carbonaceous materials for the removal of Tetracycline, Sulfamethoxazole and Bisphenol A from water. Issue 4 (August 2018) - Ahsan, Md. Ariful; Islam, Md. Tariqul; Hernandez, Cesar; Castro, Edison; Katla, Sai Krishna; Kim, Hoejin; Lin, Yirong; Curry, Michael L.; Gardea-Torresdey, Jorge; Noveron, Juan C.
Graphical abstract: Highlights: Saw dust derived functionalized graphitic carbon was prepared successfully. Better adsorbent than commercially available activated carbon. Utilized towards the removal of emerging pollutants such as TC, SMX, and BPA. H-bonding, electrostatic and π-π interaction adsorption mechanisms were proposed. Abstract: Presence of antibiotic contaminants in drinking water is increasing in epidemic proportions in recent times. Here, we report a scalable and cost-effective approach to prepare sulfonated saw dust (SD-SO3 H) derived from saw dust (SD) that exhibits high-capacity adsorbent properties for the removal of antibiotics such as Tetracycline (TC), Sulfamethoxazole (SMX), and endocrine-disruptive chemicals such as Bisphenol A (BPA). The adsorption capacities of SD-SO3 H towards the removal of TC, SMX, and BPA are 270.53 mg/g, 295.06 mg/g, and 263.75 mg/g, respectively. The adsorption capacity of SD-SO3 H is about 2 and 4 times higher than commercially available activated carbon towards the removal of SMX and BPA, respectively according to the literature. For TC, the adsorption capacity of SD-SO3 H is comparable to the commercially available activated carbon. The adsorbent was characterized using Scanning Electron Microscopy (SEM), Energy-dispersive X-ray Spectroscopy (EDS), Fourier Transform Infrared Spectroscopy (FTIR), Raman Spectroscopy, Thermogravimetric analysis (TGA), and Zeta potential measurements. The effect of initial concentration, dosage, time, pH and temperature on the adsorption process was systematically investigated. Isotherms studies showed that the TC and SMX adsorption follow Langmuir isotherm whereas, BPA adsorption follows Freundlich isotherm. The kinetics data can be well defined by the pseudo-second order kinetic model. A thermodynamic study of adsorption showed that the TC adsorption process was endothermic while the SMX and BPA adsorption processes were exothermic, and the adsorption process was spontaneous in all cases. Altogether, SD-SO3 H can be a scalable, cost-effective adsorbent for the efficient removal of TC, SMX and BPA from wastewater.